Verification of North Atlantic warm conveyor belt outflowsin ECMWF forecasts - Madonna, Erica; Boettcher, Maxi; Grams, Christian M.; Joos, Hanna; Martius, Olivia; Wernli, Heini; id_orcid:0 000-0001-9674-4837 (Quarterly Journal of the Royal Meteorological Society, 2015)
ISSN:0035-9009 ISSN:1477-870X